2013
DOI: 10.4103/0970-2113.120624
|View full text |Cite
|
Sign up to set email alerts
|

A case of spontaneous pneumothorax following radiation therapy for non-small cell lung cancer

Abstract: Spontaneous pneumothorax (SPTX) is a potentially devastating rare complication of the thoracic radiation therapy. Most of the cases in the medical literature, have been described in lymphoma patients receiving radiation therapy. The pathogenesis of this adverse event remains undefined although different mechanisms have been proposed. We present a case of post-radiation therapy SPTX in a non-small cell lung cancer (NSCLC), following intensity modulated radiation therapy (IMRT), which to our knowledge is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In one previously reported case study, the pneumothorax was diagnosed 16 months after radiation exposure (16). However, the current patient presented with recurrent spontaneous pneumothorax prior to a diagnosis of AS.…”
Section: Discussionmentioning
confidence: 62%
“…In one previously reported case study, the pneumothorax was diagnosed 16 months after radiation exposure (16). However, the current patient presented with recurrent spontaneous pneumothorax prior to a diagnosis of AS.…”
Section: Discussionmentioning
confidence: 62%
“…Spontaneous pneumothorax is unusual and the majority of cases in the medical literature have been reported in patients receiving mantle irradiation for lymphoma [9]. Pezner et al reported the incidence of pneumothorax after mantle irradiation at 2.2% in Hodgkin's disease patients without concurrent lung disease [10].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation induced pulmonary changes involving predominantly the apical pleura and parenchymal injury may be responsible [15]. Focal emphysema and fibrosis due to radiation therapy increases the chance of the formation and rupture of subpleural blebs [9]. Furthermore, increased tissue traction due to fibrosis can lead to the development of pneumothorax [16].…”
Section: Discussionmentioning
confidence: 99%
“…Most reported cases of spontaneous pneumothorax following radiotherapy are Hodgkin's disease caused by mantle irradiation [6]. Spontaneous pneumothorax following radiotherapy in lung cancer has rarely been reported [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of different mechanisms have been proposed to underlie pneumothorax with malignancies , the pathogenesis leading to spontaneous pneumothorax following radiotherapy has not been defined . There are three putative mechanisms : first, radiation‐induced pulmonary changes, as well as apical pleural and parenchymal injury, might induce focal emphysema and fibrosis, which might rupture subpleural blebs .…”
Section: Discussionmentioning
confidence: 99%